ANALISIS GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN TRENGGALEK - Mustika, Miftachul Ayu; Bhirawa, Sigit Wisnu Setya (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study was to analyze the influence of leadership style, organizational culture, and work discipline on employee performance at the Trenggalek district staffing agency. This study uses a quantitative research methodology. These studies use a causal methodology. The 52 participants were selected from a relatively small population by the authors, who used a saturated sampling approach to select the sample. The results of the partial analysis of the independent variables of leadership style, organizational culture and work discipline show that the Personnel Board of Trenggalek Regency has a significant effect on the dependent variable of employee performance. Leadership style, organizational culture, and work discipline simultaneously have a significant effect on the dependent variable of employee performance at the Personnel Agency of Trenggalek Regency